Effect of pressure on magnetic properties of MnBi prepared by low-temperature liquid phase sintering - Ngamsomrit, Satienrapong; Eknapakul, Tanachat; Pinitsoontorn, Supree; Songsiriritthigul, Prayoon (RMUTSB ACADEMIC JOURNAL, 2022)
In this work, manganese bismuth (MnBi) magnetic powders were synthesized by low-temperature liquid phase sintering in three different base pressures: ultra-high vacuum (UHV, P≈10-8 mbar), low vacuum (LV, P≈10-2 mbar) and ambient pressure (AP). The MnBi powders were successfully prepared at 375 oC for 12 hrs with a 1:1 (Mn:Bi) atomic ratio. The magnetic properties of the sintered MnBi samples were studied using a vibrating sample magnetometer (VSM). The coercivity, saturation magnetization value (Ms) and maximum energy product ((BH)max) of up to 2.42±0.07 kOe, 48.46±0.9 emu/g and 1.82±0.05 MGOe, respectively, were obtained in the MnBi sintered in ultra-high vacuum (UHV-MnBi). The morphology and chemical composition of MnBi powders were examined by scanning electron microscope (SEM) combined with energy dispersive x-ray spectroscopy (EDS). It was found that the sample sintered in ambient pressure was inhomogeneous with noticeably separated layers of Bi, Mn and MnBi, while the UHV-MnBi ingot was relatively homogeneous. The sintered products, i.e., MnBi, Bi and MnO were revealed by using x-ray diffraction. Three types of oxides which are MnO, α-MnO2 and β-MnO2, were found in all samples with different proportions and ratios. Finally, more homogenous particles with relatively less oxides were obtained in the UHV-MnBi, which are two main requirements to acquire high (BH)max.